CORRECTIONAL PROGRAMS IN THE STATE PRISONS OF INDIA: AN ANALYSIS WITH REFERENCE TO UTTARAKHAND STATE - et. al., Shalini Bahuguna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Human rights jurisprudence has greatly contributed to criminal reforms and has had an impact on India. Crime reforms across the globe also have an impact on India. The conceptualization with respect to penal reform originated in the reformist theory of punishment.[1] The time prison must have such meaning that enhances the values ​​of the reform in it. The reformer's appearance is about to add a sense of humanity in the system of criminal reformation and also to add the human values ​​into the system of prison and prison officials have to work to achieve it.[2] The level of protection guaranteed by the law for the reformatory therapy of prisoners must be carried out within a national legal framework and India does not have the same.